Techno-economic feasibility of solid oxide electrolysis hybridization with solar photovoltaics and batteries for green hydrogen production - Gonzalo Jiménez-Martín; Maciej Bąkała; Xabier Judez; Marcin Błesznowski; Mónica Aguado; Anna Niemczyk; Iñigo Garbayo (Energy Conversion and Management: X, 2025)
Solid oxide electrolysis (SOE) has reached system prototype readiness level. However, in-depth feasibility studies are still essential to assess the viability of this technology in real world applications. In this study, a techno-economic assessment of a SOE plant for hydrogen production with PV and batteries as power supply was investigated in the Spanish context. The levelized cost of hydrogen (LCOH) was estimated considering the daily power profiles at four remarkable Spanish industrial hubs: Puertollano, Tarragona, Algeciras and A Coruña. Various operating windows in the SOE system and sizes of the PV-battery plant were evaluated. Notably, it was found that maximizing the capacity factor is not directly translated into lower LCOH, but there is an optimum value. In this sense, a LCOH of ≈5 €·kg−1 could be achieved at the locations under study for different plant features. In particular, Puertollano, Tarragona and Algeciras allow a slightly lower LCOH due to the better weather conditions than A Coruña. Finally, a sensitivity analysis was conducted to analyze the effect of SOE stack cost and lifetime, concluding that further optimization of these parameters could potentially lead to LCOH of 4 €·kg−1.